2017
DOI: 10.1094/pdis-09-16-1221-re
|View full text |Cite
|
Sign up to set email alerts
|

Control of Rhizoctonia solani in Sugar Beet and Effect of Fungicide Application and Plant Cultivar on Inoculum Potential in the Soil

Abstract: Rhizoctonia solani (AG 2-2 IIIB) is the causal agent of Rhizoctonia root and crown rot, a disease that causes severe economic problems in sugar beet growing areas worldwide. In the United States, azoxystrobin is the most important active ingredient for fungicidal control of R. solani in sugar beet, showing efficacy superior to other substances. First reports on resistance development in R. solani, however, underline the importance of a careful fungicide resistance management. For this reason, the efficacy of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In the specific case of Rhizoctonia-induced diseases, quantification of the soil inoculum was found to be useful in different contexts. For example, it was used to assess rice cultivar susceptibility to R. solani AG 1-IA [26] to assess the impact of different crop rotations on the inoculum levels of a specific AG and its main host plant [27,28], and to map the inoculum level at the field scale to make site-specific fungicide applications to limit the local transmission of the pathogen [29]. A positive correlation between R. solani soilborne inoculum and disease incidence or severity was found for several R. solani AGs and their host plants under controlled experiments [19,30], but fewer studies confirmed this relationship in field experiments [31].…”
Section: Introductionmentioning
confidence: 99%
“…In the specific case of Rhizoctonia-induced diseases, quantification of the soil inoculum was found to be useful in different contexts. For example, it was used to assess rice cultivar susceptibility to R. solani AG 1-IA [26] to assess the impact of different crop rotations on the inoculum levels of a specific AG and its main host plant [27,28], and to map the inoculum level at the field scale to make site-specific fungicide applications to limit the local transmission of the pathogen [29]. A positive correlation between R. solani soilborne inoculum and disease incidence or severity was found for several R. solani AGs and their host plants under controlled experiments [19,30], but fewer studies confirmed this relationship in field experiments [31].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for a long time, the application of fungicides with different modes of action has been generally accepted to improve diseases protections synergistically, as well as to minimize the emergence of fungicide resistant strains in the elds (Gisi 1996). Azoxystrobin and difenoconazole synergism was well con rmed during the management of R. solani damping-off and root rot in sugar beet (Bartholomäus et al 2017).…”
Section: Discussionmentioning
confidence: 77%
“…High control efficacy of DIF has been reported in several ascomycetes such as Phacidiopycnis spp., Venturia inaequalis, Colletotrichum spp., Marssonina coronaria, Alternaria spp., and Fusarium spp. ( Munkvold and O’Mara, 2002 ; Villani et al, 2015 ; Fonseka and Gudmestad, 2016 ; Cao et al, 2017 ; Dang et al, 2017 ; Ali et al, 2018 ) and the basidiomycete Rhizoctonia solani ( Bartholomäus et al, 2017 ). Given the widespread occurrence of resistance to two of the three current postharvest fungicides and the stringent limitations to new postharvest fungicides registration, DIF could be a valuable additional tool to manage blue mold of pome fruit in the years to come if used appropriately and if its efficacy against other major postharvest diseases is proven.…”
Section: Discussionmentioning
confidence: 99%
“…It is pre-mixed with FDL and commercially available as Academy™ (Syngenta Crop Protection). Difenoconazole (DIF) has a systemic activity and broad-spectrum antifungal potency as shown recently ( Hof, 2001 ; Fonseka and Gudmestad, 2016 ; Bartholomäus et al, 2017 ; Dang et al, 2017 ; Jurick et al, 2017 ; Koehler and Shew, 2018 ; Ali et al, 2018 ). DMIs, such as DIF, target the sterol 14α-Demethylase Cytochrome P450 ( CYP51 ), an essential component of fungal membrane sterols required for a proper membrane functioning ( Rodriguez et al, 1985 ; Joseph-Horne and Hollomon, 1997 ).…”
Section: Introductionmentioning
confidence: 90%